2012
DOI: 10.1080/13575279.2012.683774
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Presentations to an Inner-city Psychiatric Service for Children and Adolescents

Abstract: Psychiatric emergency services for children and adolescents vary in process, structure and outcome. There are few systematic studies on the type and prevalence of psychiatric problems encountered, related circumstances or resulting interventions. Evidence in these areas is important in evaluation of the function of mental health services in the relevant catchment area. This article presents a cohort study of 466 consecutive consultations that took place in the Amsterdam Child Psychiatric Emergency Service in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
3
4
0
Order By: Relevance
“…In this study, the mean age of the children and adolescents for whom a psychiatric consultation was requested was calculated as 12. The rate of psychiatric consultations requested for girls (61.03%) was significantly higher than the rate of psychiatric consultations requested for boys, which is a compatible finding with the results reported in the literature, considering that the reported rates of psychiatric consultations requested for girls' range between 54% and 70% (18,23,(28)(29)(30)(31)(32). It is known that psychiatric referrals are more common in boys in the pre-adolescence period, however that the prevalence of psychopathologies increases in girls as opposed to boys beginning with early adolescence (33).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the mean age of the children and adolescents for whom a psychiatric consultation was requested was calculated as 12. The rate of psychiatric consultations requested for girls (61.03%) was significantly higher than the rate of psychiatric consultations requested for boys, which is a compatible finding with the results reported in the literature, considering that the reported rates of psychiatric consultations requested for girls' range between 54% and 70% (18,23,(28)(29)(30)(31)(32). It is known that psychiatric referrals are more common in boys in the pre-adolescence period, however that the prevalence of psychopathologies increases in girls as opposed to boys beginning with early adolescence (33).…”
Section: Discussionsupporting
confidence: 88%
“…Rarely does the distress represent the manifestation of a serious mental illness such as psychosis or a major mood disorder. Similar conclusions were noted by Dil and Vuijk () and Rowland et al. ().…”
Section: Theoretical Backgroundsupporting
confidence: 91%
“…Our study results showed that female adolescents were more likely to be referred to child and adolescent psychiatry clinic. The results from this study are parallel to the current literature [14][15][16][17]. This is of particular significance for mental health intervention, due to the increase in emotional and behavioral problems and the onset of psychiatric disorders that arise during adolescence [18].…”
Section: Discussionsupporting
confidence: 80%